Efecto del divorcio de los padres en el proceso enseñanza aprendizaje de los niños y niñas de educación inicial - Alajo Catota, Hilda María (2017)
The research was done to know about the effect of parental divorce on the Teaching Learning process of the children of initial education, it was applied with the objective of determining the incidence of this problem and how it affects the emotional, affective life of the children of the level Preschooler of the CEC "El Sembrador. for this reason, the methodology used was based on the qualitative and quantitative approach, accompanied by bibliographic-documentary researching, field, descriptive, exploratory, through which a positive level of researching, where was achieved to try to reduce this problem that affects so much the emotional life of the infant and improve the lifestyle of the child, as well as his family. The beneficiaries of this researching project are the children, parents, teachers of the initial level and authority of the CEC "El Sembrador" located in Pastocalle Parish, Latacunga Canton, Cotopaxi Province. In addition, the techniques and instruments were used the interview that was applied to the teacher at the initial level and authority, the parents' survey, and the observation chart based on achievement indicators applied to the children with the objective to determine the psychological level that each child has experienced the separation of their parents and what is the reaction to this painful event that they have to face throughout their lives….